(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Kalachova L. V. Technology of postgraduate education teachers’ training to the use of audio-visual teaching aids. The article describes the components of technology of postgraduate education teachers’ training to the use of audio-visual teaching aids: organizational diagnosis, procedure and content, analytical and reflective.